DOSE MEASUREMENT OF COBALT-60 RADIOTHERAPY BEAMS IN TREATMENT FIELDS - Memon, Sajjad Ahmed; Cheema, Asrar Ahmad; Laghari, Naeem Ahmed; Mangi, Fayaz Hussain (Journal of Ayub Medical College Abbottabad, 2014)
Background: Radiation therapy is a complex process with multiple steps, each of which has an impact on the quality of treatment. Accurate dosimetry is a critical step during the radiotherapy of cancer patients.The aim of the present study was to measure and evaluate the doses of two cobalt-60 (60Co) teletherapy units GWXJ80 of NPIC China and Theratron 780 of AECL Canada at various points within fields for different field sizes. Methods: This cross-sectional descriptive study was done to measure the 60Co doses in the treatment fields.The dose measurements were done in air and 30Ã—30Ã—30 cm3 Phantom at 80 cm SSD by using calibrated NE 2570 Farmer Electrometer & NE 2571 Farmer Ionization Chamber and percentage of doses were calculated. Results: The results showed that 60% central area of all fields ranging from 100-98.79% and 100-96.12% for GWXJ80 in the air and phantom, whereas for Theratron 780, they were ranging from 100-98.50% and 100-96.45% in air and phantom respectively. The percentages of doses at the edges for GWXJ80 and Theratron 780 in the air were 75.39-38.66% & 85.65-46.47% respectively and they were 82.22-40.39% & 49.05-24.55% respectively in phantom. Conclusions: The doses within 60% central area of fields in air were higher than phantom for both teletherapy units. The doses at field edges in air were lower in GWXJ80 than Theratron 780 whereas in phantom they were vice versa. But all were in the acceptable range as recommended by International Commission on Radiation Units and Measurements. Keywords:Cobalt-60 ( 60Co), Quality Assurance, Dosimetry, Exposure, Central Area, Edge